Protective Effects of Spirulina Platensis- Selenium Nanoparticles Against Nicotine Induced-Lung Toxicity - Mohamed, Ahmed H.; Ibrahem, Menna Allah K.; Elgazar, Amr A.; Shabib, Hadeer M.; Morsy, Eman A.; Salah, Sara A.; Ibrahem, Yasmin H.; Mohamed, Doaa M.; Gobba, Naglaa A.; Salem, Mohamed A.; Ahmed, Fakher M.; Ali, Ali A.; et al. (Pakistan Journal of Nutrition, 2021)
Background and Objective: Smoking contributes significantly to the development of cardiovascular disease and lung cancer in smokers. The purpose of this study was to look into the protective effect of Spirulina platensis nanoparticles (SP-SeNPs) on nicotine-induced lung toxicity in mice. Materials and Methods: SP-SeNPs were prepared and characterized to find mean particle size of SP-SeNPs and zeta potential. Furthermore, the IC50 of SP-SeNPs against the A549 lung carcinoma cell line and LD50 was calculated. A total of 90 adult albino mice weighing approximately 35±5 g was used in this study. Results: Results showed that the shapes of SP-SeNPs were spherical and the mean particle size was 39.86±0.14 nm and negative zeta potential was +33.14. Also, IC50 of SP-SeNPs against the A549 lung carcinoma cell line and LD50 was 72.7 μg mL–1 and 490 mg kg–1 body weight, respectively. The daily oral administration of SP-SeNPs at concentrations of 9.8 and 24.5 mg kg–1 body weight for 30 days to mice treated with nicotine (2.5 mg kg–1 body weight) resulted in a significant improvement in plasma total cholesterol (TC), triacylglycerols (TG), high density lipoprotein-cholesterol (HDL-C), phospholipids (PLs) and vitamin C, as well as lung TNF-α, interleukin 6 (IL-6), interleukin 10 (IL-10). On the other hand, inducible oral administration of SPSNPs, increased the activity of superoxide dismutase (SOD) and glutathione peroxidase (GPx), decreased glutathione (GSH) and the level of malondialdehyde (MDA) in nicotine-treated lungs of mice. Furthermore, SP-SeNPs almost normalized these effects in lung histoarchitecture. Conclusion: The SP-SeNPs have lung protective activity against nicotine-induced lung toxicity in mice.